Peranan marketing public relations Bukalapak.com dalam mempertahankan brand reputation melalui kegiatan integrated marketing communications - Astrid Haryanti; Siti Dewi Sri Ratna Sari (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2019)
This study used a qualitative approach with descriptive research by describing each activity of IMC strategy which had been carried out by Bukalapak.com’s MPR. The primary data collecting methods used semi structured interviews and non-participant observation. The secondary data used company profile, news from internet and journals. The data method analysis in this study used coding techniques with open coding, axial coding and selective coding. To validate the data, this study used triangulation technique by using the source. The results of this study is the MPR of Bukalapak.com used several integrated marketing communication activities such as advertising, public relations, sales promotions, sponsorship, interactive marketing, direct marketing and personal selling to maintain the brand reputation as a leading e-commerce company in Indonesia.